Bio-economic evaluation of dairy farm management scenarios using integrated simulation and multiple-criteria models - Herrero, Mario; Fawcett, R.H.; Dent, J.B. (Elsevier, 1999)
Appropriate selection of holistic management strategies for livestock farming systems requires: (1) understanding of the behaviour of, and interrelations between, the different parts of the system; (2) knowledge of the basic objectives of the decision maker managing such enterprise; and (3) understanding of the system as a whole in its agro-ecoregional context. A decision-support system based on simulation and mathematical programming techniques has been built to represent pastoral dairy production systems. The biological aspects (grass growth, grazing, digestion and metabolism, animal performance) are represented by simulation studies under a variety of management regimes. The outputs from the simulation runs (such as pasture utilisation, stocking rates, milk yields, fertilizer use, etc.) are used as data input to the multi-criteria decision-making models, and the latter have been used to select the management strategies which make the most efficient use of the farm's resources (i.e. land, animals, pastures). The paper discusses the effects and implications of different management scenarios and policies on the bio-economic performance of highland dairy farms in Costa Rica. Nevertheless, the model frameworks are generic and can be adapted to different farming systems or ruminant species. The effect of model formulation and sensitivity, different decision-maker objectives, and/or activity or constraint definitions on management strategy selection are also analysed.